An haplotype view of cystinuria in dog - S. Frattini; M. Cortellari; A. Talenti; A. Negro; C. Biagini; M. Polli; P. Crepaldi (2019)
Canine cystinuria is an autosomal recessive disorder that affects a dog’s ability to filter cystine out of urine. The Solute Carrier Family 3 Member 1 (SLC3A1) is a gene, coding for a portion of the membrane protein that controls the reabsorption of dibasic amino acids at renal level, pivotal in the pathology onset. Aim of the work is to deepen the haplotype variability associated with cystinuria in English Bulldog (EB), French Bulldog (FB), and some other afflicted breeds. Our work started from a sample of 19 dog, 9 FB and 10 EB, genotyped at the locus c.A2092G on the exon 10 of the gene SLC3A1 on chromosome 10. Samples were then genotyped with 230k SNPChip (Illumina) and haplotypes, built around gene SLC3A1 (±1.0 Mb), were explored. We investigated differences in haplotypes among 3 group of animals: dogs homozygous for the mutation at the SLC3A1 locus (classified as PP), heterozygous (NP) and wild type (NN). The 6 samples classified as PP showed a unique and identical haplotype of 44 SNPs at ± 1.0 Mb around the gene, with a core haplotype of 4 SNPs within the gene. The analysis was expanded to a partially public data set comprising some of the most susceptible breeds for the pathology: Newfoundland, Labrador Retriever, Australian Cattle Dog, Miniature Pinscher, Rottweiler and Dachshund, in addition to further EB and FB. Of the 93 analyzed animals, only 4 (3 EB and 1 FB) showed the same haplotype. Considering the core haplotype, 4 Newfoundland out of 10 in the data set presented this haplotype. These results suggest that the severity of this pathology could be evaluated not only at the known causal mutation but as a conserved haplotype. The present work showed the applicability of dense SNP panels in the identification of haplotypes linked to causal mutations for canine cystinuria. The detection of target haplotypes associated with major known pathologies afflicting canine species, for each breed, could make possible the use of this versatile tool as a first general health check control in dog. Aknoledgments: ...